Thermoplastic hot melt film having excellent adhesion with nanosilica

CN123026985APending Publication Date: 2026-11-03朴喜大
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611109362.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-08-14
Filing Date
2018-09-09
Publication Date
2026-11-03

Smart Images

  • Figure CN123026985A_ABST
    Figure CN123026985A_ABST
Patent Text Reader

Abstract

The present application proposes a thermoplastic hot melt film with excellent adhesion force with nano-silica, which is prepared with nano-silica to prepare a thermoplastic hot melt film, so as to insert the hot melt film between the fabric and the fabric, when it is bonded by pressing work (No-Sew Press), if the yarn density of the fabric is high or low, or the size of the fabric weaving hole is large or small, the thermoplastic hot melt film is prevented from tilting to the fabric side and melting into it due to heat and pressure, and the thermoplastic hot melt film is evenly distributed to both sides, so as to improve the bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the patent application filed on September 9, 2018, with application number 201880019850.2 and invention title "Thermoplastic hot melt film with excellent adhesion incorporating nano-silica". Technical Field

[0002] This invention relates to a thermoplastic hot melt film with excellent adhesion, incorporating nano-silica. More specifically, it relates to the use of a thermoplastic hot melt film incorporating nano-silica for bonding when inserting the film between adhesives (e.g., fabrics and fabrics). This prevents the hot melt film from tilting to one side of the fabric and melting into it due to heat and pressure, especially when using a no-sew press, if the yarn density of the fabric is high or low, or the diameter of the fabric hole is large or small. Furthermore, it ensures that the hot melt film is evenly distributed on the fabric surface, thereby maximizing the adhesive strength of the hot melt film. Background Technology

[0003] Recently, efforts have been made in various industrial sectors, including the footwear industry, to reduce manufacturing costs. One aspect of this is the reduction or elimination of sewing processes, which require significant manpower. This approach has proven effective in some areas. For example, replacing sewing processes, which account for a considerable portion of manufacturing costs, with bonding processes increases per capita productivity and shortens process time, thereby reducing costs.

[0004] On the other hand, in a typical bonding process, liquid adhesive is applied to the adhesive. After (hereinafter referred to as "fabric"), the fabric is bonded together by drying to allow the solvent or moisture to evaporate. This method has the advantage of reducing process time and manpower compared to sewing, but it does not only strive to reduce costs. Furthermore, it utilizes a film-form hot melt (hereinafter referred to as "thermoplastic hot melt film") to replace liquid adhesives, thereby bonding the fabrics through hot pressing.

[0005] Thermoplastic hot melt films are used in the footwear industry for their environmental friendliness, ease of use, and cost reduction. Types include thermoplastic polyurethane (TPU) hot melt films, polyamide hot melt films, ethylene-vinyl acetate (EVA) hot melt films, and polyester hot melt films, among others. Thermoplastic polyurethane and ethylene-vinyl acetate hot melt films are the most commonly used. These thermoplastic hot melt films offer advantages such as high productivity due to their excellent extrusion workability, environmental friendliness due to the absence of solvents, excellent adhesion and physical properties, and a pleasant feel. Furthermore, to ensure adhesion to various fabrics (e.g., engineered mesh, sandwich mesh, lining fabrics), thermoplastic hot melt films with a thickness of 0.2 mm or more are primarily used.

[0006] However, in the past, thermoplastic hot melt films were usually prepared with a thickness of more than 0.2 mm in order to ensure excellent adhesion. As a result, when the hot melt film was placed between fabrics and pressed (no-sew press), the fabric product became heavier overall, felt very stiff to the touch, and could not adapt to the development trend of the increasingly lightweight footwear industry.

[0007] In particular, as mentioned above, the thickness of conventional thermoplastic hot melt films (above 0.2 mm) is also problematic. Specifically, when pressing (no-sew press) is performed with the thermoplastic hot melt film inserted between fabrics, a thicker film results in a larger hole diameter on the fabric side, causing excessive hot melt film to penetrate, leaving no hot melt film at the bonding interface and ultimately leading to poor bonding. That is, when bonding fabrics with large and small holes, or fabrics with high and low yarn density, or when using thermoplastic hot melt films to bond other types of fabrics, the hot melt film tilts excessively to the fabric side due to heat and pressure. Specifically, the hot melt film melts and flows into the fabric side with the larger hole size or the lower yarn density, leaving no hot melt film residue at the bonding interface, resulting in poor bonding. Summary of the Invention

[0008] Technical issues The present invention addresses the problems of the prior art as described above, and aims to provide a thermoplastic hot melt film with excellent adhesion of nano-silica that utilizes a thinner thickness of thermoplastic hot melt film without adhesion strength issues to ensure the same adhesion strength as conventional products.

[0009] Another object of the present invention is to provide a thermoplastic hot melt film with excellent adhesion incorporating nano-silica that can achieve uniform adhesion using a hot melt film with a thickness (0.2 mm or more) that is thinner than conventional thermoplastic hot melt films.

[0010] Solution to the problem The thermoplastic hot melt film with excellent adhesion of the present invention is characterized in that it comprises a thermoplastic resin, preferably a composition selected from thermoplastic polyurethane, ethylene vinyl acetate, polyamide, polyester and nano silica, especially, the content of nano silica is 0.1 to 5.0 phr.

[0011] The effects of the invention The advantage of this invention is that when preparing thermoplastic hot melt film, it is combined with nano-silica, so that compared with the thickness of conventional hot melt film (above 0.2 mm), it can maintain excellent adhesion at a thickness of about 25 to 50%, which not only reduces the cost of the product, but also prevents the fabric from hardening after pressing, and exhibits a soft feel compared with the past.

[0012] Furthermore, the effect of this invention is that it can improve the adhesion, so that when the yarn density of the fabric is high or low, or the size of the weaving hole is large or small, it can prevent the thermoplastic hot melt film from tilting to one side of the fabric and melting into it due to heat and pressure during the pressing operation (No-Sew Press). Specifically, it can prevent the thermoplastic hot melt film from melting into the side with low yarn density or large weaving hole size, and can make the thermoplastic hot melt film evenly distributed on the fabric surface. Attached Figure Description

[0013] Figure 1 Photographs of engineering meshes used to test the adhesion of the thermoplastic polyurethane hot melt film with nano-silica of the present invention and a conventional thermoplastic polyurethane hot melt film, respectively.

[0014] Figure 2 Photographs are shown of sandwich meshes used to test the adhesion of the thermoplastic polyurethane hot melt film with nano-silica of the present invention and a conventional thermoplastic polyurethane hot melt film, respectively.

[0015] Figure 3Photographs are shown of lining fabrics used to test the adhesion of the thermoplastic polyurethane hot melt film with nano-silica of the present invention and a conventional thermoplastic polyurethane hot melt film, respectively.

[0016] Figure 4 The diagram illustrates the state of adhesion between the thermoplastic polyurethane hot melt film of the present invention, which is bonded between an engineering mesh (corresponding to the outer material) and an inner lining fabric (corresponding to the inner material), and a conventional thermoplastic polyurethane hot melt film, respectively.

[0017] Figure 5 The diagram illustrates the state of adhesion between the thermoplastic polyurethane hot melt film of the present invention, which is bonded between a sandwich mesh (corresponding to the outer material) and an inner lining fabric (corresponding to the inner material), and a conventional thermoplastic polyurethane hot melt film, respectively.

[0018] Figure 6 To demonstrate the adhesion of the thermoplastic polyurethane hot melt film to the above-mentioned parts, sections "①, ②, ③, and ④" were removed respectively. Figure 4 The photograph shows the state between the engineered mesh and the lining fabric.

[0019] Figure 7 To remove portions “①, ②, ③, ④” respectively, in order to confirm that the thermoplastic polyurethane hot melt film adheres to the above-mentioned Figure 5 The photograph shows the state between the interlayer mesh and the inner lining fabric.

[0020] Figure 8 To use an electron microscope × 100 to photograph the above Figure 1 A cross-sectional photograph of the engineering network shown.

[0021] Figure 9 To use an electron microscope × 100 to photograph the above Figure 2 A cross-sectional photograph of the sandwich mesh shown.

[0022] Figure 10 To use an electron microscope × 100 to photograph the above Figure 3 A cross-sectional photograph of the lining fabric shown.

[0023] Figure 11 To take photographs of cross sections when bonding engineering mesh and inner lining fabric using conventional thermoplastic polyurethane hot melt film using an electron microscope ×100.

[0024] Figure 12 To take a cross-sectional photograph of the bonding of engineering mesh and inner lining fabric using conventional thermoplastic polyurethane hot melt film using a scanning electron microscope (SEM) ×150.

[0025] Figure 13 To take a cross-sectional photograph of the bonding of the engineering mesh and the inner lining fabric using the thermoplastic polyurethane hot melt film containing nano-silica of the present invention.

[0026] Figure 14 To take a cross-sectional photograph of the bonding of the engineering mesh and the inner lining fabric using the thermoplastic polyurethane hot melt film of the present invention containing nano-silica, using a scanning electron microscope ×150.

[0027] Figure 15 To take a cross-sectional photograph of the bonding of the sandwich mesh and the inner lining fabric using a conventional thermoplastic polyurethane hot melt film using an electron microscope ×100.

[0028] Figure 16 To take a cross-sectional photograph of the bonding of the sandwich mesh and the inner lining fabric using a conventional thermoplastic polyurethane hot melt film using a scanning electron microscope (×150).

[0029] Figure 17 To take a cross-sectional photograph of the bonding of the sandwich mesh and the inner lining fabric using the thermoplastic polyurethane hot melt film with nano-silica of the present invention.

[0030] Figure 18 To take a cross-sectional photograph of the bonding of the sandwich mesh and the inner lining fabric using the thermoplastic polyurethane hot melt film with nano-silica of the present invention. Detailed Implementation

[0031] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings and photographs. In the detailed description that follows, representative embodiments of the present invention are presented to address the aforementioned technical problems. Furthermore, other embodiments proposed in the present invention may be described in lieu of other embodiments within the framework of the present invention.

[0032] In this invention, a thermoplastic hot melt film with excellent adhesion is achieved by incorporating nano-silica. When preparing the thermoplastic hot melt film, nano-silica is incorporated to insert the film between fabric layers. During bonding via a no-sew press, the hot melt film is prevented from tilting excessively to one side of the fabric and melting due to heat and pressure, regardless of the fabric's yarn density or the size of its weave holes. This ensures the hot melt film is evenly distributed across the fabric surface, thereby improving adhesion. Here, "evenly distributed across the fabric surface" means that during the pressing process, the thermoplastic hot melt film is prevented from melting and flowing into the side of the fabric with higher yarn density or larger weave holes. Instead, it is evenly distributed with 1 / 3 of the film on the upper side, 1 / 3 on the lower side, and 1 / 3 between the fabric layers (bonding interface). This is clearly demonstrated by the following photographs.

[0033] Thus, the thermoplastic hot melt film of the present invention is characterized by not only being uniformly distributed on the surface of the fabric to improve adhesion, but also having no problem with adhesion strength. Even when prepared with a thickness that is thinner than that of conventional thermoplastic hot melt films (i.e., 0.2 mm or more), it can ensure the same adhesion strength as conventional hot melt films.

[0034] In particular, in this invention, a hot melt film incorporating nano-silica is prepared to improve... Specifically, the adhesive strength of the thermoplastic hot melt film is preferably around 0.1 to 5.0 phr for the nano-silica, and the size (primary particles) of the nano-silica is 100 nm or less. As an example of a method using the aforementioned nano-silica, the following method is employed: For thermoplastic polyurethane resin, when polymerizing the resin, nano-silica is mixed with the raw materials before polymerization to prepare a resin for thermoplastic hot melt film; or a masterbatch is prepared using nano-silica, and then mixed with the thermoplastic polyurethane resin to prepare a resin for thermoplastic hot melt film. Furthermore, for ethylene vinyl acetate, polyamide, and polyester resins, the following method is used: a masterbatch is prepared using nano-silica, and then mixed with the respective resin to prepare a resin for thermoplastic hot melt film. This method is specifically described below.

[0035] In this invention, to ensure excellent adhesion even with a thin thermoplastic hot melt film (thickness less than 0.2 mm), and specifically to address the problems inherent in conventional thermoplastic hot melt films, in order to prevent the hot melt film from melting and flowing into the side of the fabric with lower yarn density or larger weave pore size during no-sew pressing, nano-silica is incorporated when preparing the thermoplastic hot melt film. In this way, by incorporating nano-silica during the preparation of the thermoplastic hot melt film, the phenomenon of the hot melt film being tilted to one side due to the uniform dispersion of nano-silica can be prevented, thereby ultimately achieving the effect of hot melt film residue at the bonding interface, thus improving the adhesion.

[0036] As described above, when nano-silica is used in the preparation of thermoplastic hot melt films, it has been confirmed that even a small amount (0.1 phr or more) improves the adhesion, and the best adhesion is observed when the amount is consistently around 0.5 to 1.0 phr. Furthermore, it has been confirmed that when the content of the aforementioned nano-silica is 5.0 phr or more, not only does the surface of the thermoplastic hot melt film become opaque, but the adhesion also decreases, and blooming occurs on the surface of the hot melt film over time. In this invention, to demonstrate the effects and characteristics described above, experimental data consisting of microscopic photographs and scanning electron microscope photographs are presented, and will be specifically described with reference to Figures 1 to 18.

[0037] On the other hand, the thermoplastic polyurethane used in this invention is in its virgin form. The aforementioned virgin thermoplastic polyurethane is a type of thermoplastic polyurethane prepared by polymerizing short-chain glycols (such as 1,4-butanediol) as chain extenders with polyester polyols, polyether polyols, polycarprolactone, etc., and aromatic isocyanates and aliphatic isocyanates.

[0038] Furthermore, in this invention, when preparing the thermoplastic hot melt film, in addition to the aforementioned original thermoplastic polyurethane (virginTPU), various thermoplastic polyurethane fragments can be used alone, such as scraps remaining after high-frequency processing of thermoplastic polyurethane used in shoes or scraps remaining after processing hot melt thermoplastic polyurethane, or these can be mixed with the original thermoplastic polyurethane. Moreover, in addition to the aforementioned thermoplastic polyurethane, ethylene vinyl acetate, polyamide, polyester resin, etc., can also be used when preparing the thermoplastic hot melt film.

[0039] This invention specifically proposes a method for preparing thermoplastic polyurethane hot melt films, which are the most widely used thermoplastic polyurethane hot melt films for footwear, among thermoplastic polyurethane hot melt films, ethylene vinyl acetate hot melt films, polyamide hot melt films, and polyester hot melt films. Preferably, a method for preparing thermoplastic polyurethane hot melt films incorporating nano-silica is proposed. That is, in this invention, as described above, a method for preparing thermoplastic polyurethane hot melt films is detailed by mixing nano-silica with the raw materials (isocyanate, polyol, ethylene glycol) used in the polymerization of thermoplastic polyurethane, and by using nano-silica to prepare a masterbatch and mixing it with thermoplastic polyurethane resin in different proportions to prepare thermoplastic polyurethane hot melt films.

[0040] First, the preparation method of the thermoplastic polyurethane hot melt film of the present invention will be specifically described. The preparation method of the thermoplastic polyurethane hot melt film is a method for preparing the film by mixing the raw material used in the polymerization of thermoplastic polyurethane particles (pell et) to polymerize it, and the preparation method consists of four steps.

[0041] That is, preparing the raw materials used for the typical polymerization of thermoplastic polyurethane particles, in detail, precisely... Prepare polyol, isocyanate, and short-chain glycol (hereinafter referred to as "first step").

[0042] Choose one of the raw materials mentioned in the first step above to add nano-silica, or add nano-silica to multiple raw materials mentioned above and mix them (hereinafter referred to as the "second step"). At this time, the temperature is preferably 80 to 100°C and the stirring speed is preferably 20 to 30 rpm.

[0043] In the second step described above, the raw material with fully mixed nano-silica and the remaining raw material are simultaneously fed into a reactive extruder, or multiple raw materials with fully mixed nano-silica are simultaneously fed into a reactive extruder to polymerize the thermoplastic polyurethane particles (hereinafter referred to as the "third step").

[0044] After drying and curing the thermoplastic polyurethane particles polymerized in the third step above to prepare a resin for thermoplastic polyurethane hot melt film, the resin is fed into a conventional T-die extruder to prepare the thermoplastic polyurethane hot melt film to be realized in this invention (hereinafter referred to as "fourth step"). That is, in a conventional T-die extruder, if the thermoplastic polyurethane hot melt film resin containing nano-silica is extruded into a film form, or if the resin is used to coat conventional release paper, the thermoplastic polyurethane hot melt film containing nano-silica to be realized in this invention is prepared.

[0045] Second, a method for preparing thermoplastic polyurethane hot melt film by using the nano-silica of the present invention to prepare a masterbatch and mixing it with thermoplastic polyurethane resin in different contents is described in detail.

[0046] That is, the thermoplastic polyurethane (e.g., original thermoplastic polyurethane, thermoplastic polyurethane fragments, thermoplastic polyurethane mixtures thereof, etc.) or ethylene vinyl acetate, polyamide, polyester resin and nano silica are metered according to different contents. In this case, preferably, the content of the above-mentioned nano silica does not exceed 40%.

[0047] Then, the aforementioned nano-silica and thermoplastic polyurethane (or ethylene vinyl acetate, polyamide, polyester resin) are fed into a conventional kneader and heated at 100°C. Mix the mixture at a temperature of 120°C and a speed of 20-30 rpm.

[0048] Subsequently, the thermoplastic polyurethane (or ethylene vinyl acetate, polyamide, polyester resin) mixed with the aforementioned nano-silica is cooled and then pulverized to a diameter of less than 10 mm. It is then fed back into a conventional twin extruder. At this time, the temperature of the twin extruder is 150–200°C.

[0049] Then, while the resin compounded in the above-mentioned biaxial extruder is fed into cooling water at 15-20°C to prepare it into granules, it becomes the masterbatch defined in this invention. The masterbatch is then mixed with thermoplastic polyurethane in different proportions to prepare resin for thermoplastic polyurethane hot melt film.

[0050] Subsequently, the aforementioned resin is fed into a conventional T-die extruder to prepare the thermoplastic polyurethane hot melt film to be realized in this invention. That is, in a conventional T-die extruder, if the thermoplastic polyurethane hot melt film prepared by mixing a masterbatch containing nano-silica and thermoplastic polyurethane is extruded into a film form using resin, or if the aforementioned resin is used to coat conventional release paper, then the thermoplastic polyurethane hot melt film containing nano-silica to be realized in this invention can be prepared.

[0051] The following, as described above, will demonstrate the effect on thermoplastic polyurethane hot melt films incorporating nano-silica, with reference to Figures 1 to 18, and will specifically explain the experimental data (preferably the adhesion test).

[0052] Figures 1 to 7 show the preparation steps for the adhesion test. The fabric to be bonded uses a general-purpose fabric for shoes, with engineered mesh and sandwich mesh primarily used as outer material (as shown in Figures 1 and 2), and an inner lining fabric primarily used as inner material (as shown in Figure 3). Furthermore, as... Figure 4 As shown in Figure 5, the bonding structure and pressing conditions are as follows: After inserting a thermoplastic polyurethane hot melt film between the engineering mesh (equivalent to the outer material), the sandwich mesh, and the inner lining fabric (equivalent to the inner material), a pressing operation is performed at 130°C and a pressure of 60 kgf for 30 seconds. The thermoplastic polyurethane hot melt film used is either a conventional thermoplastic polyurethane hot melt film or a thermoplastic polyurethane film containing different amounts of nano-silica as described in this invention. Ester hot melt film. Furthermore, as shown in Figures 6 and 7, the bonding state of the fabric bonded by the thermoplastic polyurethane hot melt film was confirmed by removing parts “①, ②, ③, ④” respectively. The results are shown in Table 1 below. In Table 1, the parts without values ​​in the engineering mesh bonding (kgf / cm) and sandwich mesh bonding (kgf / cm) columns, i.e., the parts shown in dark (④), indicate that the material is damaged due to good adhesion.

[0053] Table 1

[0054]

[0055] As shown in Table 1 above, with respect to conventional thermoplastic polyurethane hot melt films, when engineered mesh and sandwich mesh, which are commonly used as outer materials for shoes, are bonded to lining fabric, which is used as inner material, appropriate bond strength (minimum 2.5 kgf / cm) is only observed when the thickness of the thermoplastic polyurethane hot melt film is 0.2 mm or more. When the thickness of the melt film is less than 0.2 mm (i.e., thicknesses of 0.10 mm or 0.15 mm), the bonding strength fails to reach the benchmark value. In fact, the thickness of the thermoplastic polyurethane hot melt film most commonly used by shoe manufacturers is 0.2 mm.

[0056] Conversely, as described in this invention, when thermoplastic polyurethane hot melt films containing nano-silica at different contents (i.e., 1 phr, 2 phr, 3 phr) and engineered mesh and sandwich mesh as outer material raw materials are bonded to inner lining fabric as inner material raw materials, tests are conducted at different thicknesses. It is finally confirmed that when the content of nano-silica is added at 1 phr and 2 phr respectively, the bonding strength is good even at a thickness of 0.1 mm, and stable bonding strength is confirmed at 0.15 mm and 0.2 mm.

[0057] On the other hand, it was confirmed that when the content of nano-silica was 3 phr, the adhesive strength decreased as the content of nano-silica increased. Further increasing the content resulted in a slight decrease in adhesive strength up to 5 phr, but the adhesion itself remained unaffected. However, it was confirmed that when the content of nano-silica was above 5 phr, it hindered adhesion and also caused a decrease in the transparency of the thermoplastic polyurethane hot melt film and blooming.

[0058] As described above, in this invention, the adhesion of the thermoplastic polyurethane hot melt film with nano-silica can be confirmed by the above adhesion test results. In order to confirm the above test results, the bonding cross-section arrangement of the thermoplastic polyurethane hot melt film bonded between the fabrics after the pressing work (No-Se w Press) was confirmed by electron microscopy, and the results are as follows.

[0059] First, Figure 8 shows an image of the project shown in Figure 1 taken using an electron microscope (×100). Figure 9 shows a cross-sectional photograph of the mesh, taken using an electron microscope (×100) as shown in Figure 2. A photograph of the cross-section of the sandwich mesh, Figure 10, taken using an electron microscope (×100). Photograph of the cross-section of the lining fabric shown in Figure 3.

[0060] Furthermore, Figures 11 to 18, detailed below, are various photographs taken using electron microscopy and scanning electron microscopy, illustrating the use of two different types of external... When the engineered mesh and interlayer mesh of the outer fabric are bonded together with the inner lining fabric (which is the lining fabric) using a thermoplastic polyurethane hot melt film (i.e., conventional thermoplastic polyurethane hot melt film and the thermoplastic polyurethane hot melt film of the present invention incorporating nano-silica), cross-sectional photographs of the portions where adhesion strength tests were performed to confirm the adhesion results (i.e., portion ③ of FIG. 6 and portion ② of FIG. 7) are taken using an electron microscope and a scanning electron microscope. Additionally, Tables 2 and 3 present photographs of the bonded cross-sections taken using an electron microscope and a scanning electron microscope when using conventional thermoplastic polyurethane hot melt film and when using the thermoplastic polyurethane hot melt film of the present invention incorporating nano-silica.

[0061] Table 2

[0062] Table 3

[0063] As shown in Tables 2 and 3 above, the elliptical portions are electron microscope and scanning electron microscope images of the bonding interface between the fabrics. By examining the scanning electron microscope images of the two fabrics, it can be confirmed that the amount of thermoplastic polyurethane hot melt film remaining at the bonding interface in the poorly bonded fabric is relatively very small. Most of the thermoplastic polyurethane hot melt film melts and penetrates towards the fabric side with larger weave holes (outer fabric), thus leaving little amount remaining at the bonding interface (see Figures 11, 12, 15, and 16 respectively).

[0064] Conversely, as in this invention, when examining a fabric bonded with a thermoplastic polyurethane hot melt film containing nano-silica (i.e., a well-bonded fabric), it can be confirmed that the thermoplastic polyurethane hot melt film does not tilt to one side of the fabric but remains intact at the bonding interface, thus being contained in both sides of the fabric, thereby achieving a state of good bonding strength.

[0065] Furthermore, it can be confirmed that, based on the properties of conventional thermoplastic polyurethane hot melt films, when subjected to pressing (No-Sew Press), they react sensitively to heat and pressure, causing a rapid increase in fluidity. Thus, depending on the fabric structure, for areas where adhesion is poor due to excessive penetration between fabrics without remaining at the bonding interface, as in this invention, nano-silica is used to ensure that a specified amount of thermoplastic polyurethane hot melt film remains at the bonding interface, thereby improving adhesion even at thin thicknesses.

[0066] In this way, when nano-silica is used as a copolymer with thermoplastic polyurethane, the internal chemical bonding and van der Waals bonds of urethane resin increase, thereby increasing the rheology and coadhesion of thermoplastic polyurethane, resulting in stronger bond strength and ultimately increasing the adhesive force in the structure.

[0067] In this way, nano-silica can be used in thermoplastic polyurethane hot melt films to achieve the same bonding performance with a thinner thickness than conventional thermoplastic polyurethane hot melt films. This not only reduces the cost of the resin used in thermoplastic polyurethane hot melt films, but also provides multiple advantages such as increased flexibility of the bonded fabric and lighter shoes.

[0068] On the other hand, Table 4 below presents the results of a second adhesion test (No-Sew Pres s) of a thermoplastic polyurethane hot melt film with a detailed adjustment of the nano-silica content. The adhesion test conditions are the same as those in Table 1 above. In Table 4, the portions without values ​​in the engineered mesh adhesion (kgf / cm) and sandwich mesh adhesion (kgf / cm) columns, i.e., the portions shown in dark (①, ②), indicate material damage due to good adhesion.

[0069] Table 4

[0070]

[0071]

[0072] As shown in Table 4 above, observe the effects of different amounts of nano-silica added and the effects of not adding it. The results of the second bonding test for the same type of fabric were the same as those of the first bonding test in Table 1 above. For conventional thermoplastic polyurethane hot melt films, when bonding engineered mesh and sandwich mesh, which are commonly used as outer materials for shoes, to lining fabrics, which are used as inner materials, appropriate bonding strength (minimum 2.5 kgf / cm) is only observed when the thickness of the thermoplastic polyurethane hot melt film is 0.2 mm or more. However, when the thickness of the thermoplastic polyurethane hot melt film is less than 0.2 mm (i.e., thickness: 0.10 mm, 0.15 mm), the bonding strength does not reach the benchmark value.

[0073] However, as described in this invention, the content varies (preferably less than 1 phr, depending on the specific content). To test the bonding strength of the same fabric at different thicknesses, nano-silica was added to the fabric. The results showed that when 0.1 phr and 0.3 phr were added, the bonding strength was somewhat unstable at thicknesses of 0.1 mm and 0.15 mm, respectively, but showed a tendency to improve compared to previous tests. Good bonding strength was confirmed at concentrations above 0.5 phr. In other words, when the nano-silica content was 1 phr, the same good bonding results as the first bonding test were obtained.

[0074] As described above, it was confirmed that a suitable nano-silica content of approximately 0.5–3 phr in the first and second adhesion tests significantly improved adhesion. However, in this invention, it was determined that a nano-silica content of 0.1–5.0 phr could also be used. When the content exceeds 5 phr, the high nano-silica content may reduce adhesion and transparency, potentially leading to blooming on the surface. Therefore, in this invention, experiments confirmed that a nano-silica content of 0.1–5.0 phr achieves the most ideal purpose and effect when preparing thermoplastic polyurethane hot melt films.

[0075] Table 5 below shows the bonding test results of various hot melt films prepared with different contents of nano-silica when preparing ethylene vinyl acetate hot melt films, polyamide hot melt films, and polyester hot melt films, in addition to thermoplastic polyurethane hot melt films, for different fabrics.

[0076] Table 5

[0077]

[0078]

[0079] As shown in Table 5 above, it can be confirmed that the adhesion of ethylene vinyl acetate hot melt films, polyamide hot melt films, and polyester hot melt films is reduced compared to thermoplastic polyurethane hot melt films. However, the adhesion is improved by adding nano-silica. Specifically, results show that the nano-silica content is ideally between 1.0 and 3.0 phr, and it is confirmed that when the content exceeds 5 phr, the adhesion decreases, similar to the reduced transparency and blooming issues of thermoplastic polyurethane hot melt films. When the nano-silica content is 4.0 phr and 5.0 phr, the adhesion is not reduced compared to conventional thermoplastic hot melt films.

[0080] On the other hand, Table 6 below presents the results of a second adhesion test (No-Sew Press) conducted by adjusting and coordinating the content of nano-silica to further reduce the content of each different resin in the thermoplastic polyurethane hot melt film.

[0081] Table 6

[0082]

[0083] As shown in Table 6 above, it was confirmed that the bonding strength was somewhat unstable when 0.1 phr and 0.3 phr of nano-silica were added. However, compared with the previous hot melt film without nano-silica, the bonding strength was improved, and it was confirmed that the bonding strength was better at concentrations above 0.5 phr. Products with a phr of 1.0 or higher received similar improvements.

[0084] As described above, it was confirmed that when preparing ethylene vinyl acetate hot melt films, polyamide hot melt films, and polyester hot melt films, the optimal effect is achieved when the content of nano-silica is 1.0 to 3.0 phr. Furthermore, when the content is 0.1 to 1.0 phr, compared to conventional hot melt films, good adhesion is expected. When the content exceeds 5.0 phr, some problems arise, but the adhesion strength is not reduced compared to conventional hot melt films. Therefore, this experiment confirms that when preparing the above-mentioned hot melt films, a nano-silica content of 0.1 to 5.0 phr can achieve the objectives and effects desired in this invention.

[0085] Sequence Directory Free Text Existing technical documents and patent documents (Patent Document 1) Publication No. 10-2015-0005092 (Invention Title: Thermoplastic Polyurethane Hot Melt Film. Publication Date: January 14, 2015) (Patent Document 2) Patent Publication No. 10-2014-0147631 (Invention Title: Method for preparing thermoplastic polyurethane hot melt film and thermoplastic hot melt film prepared by the above method. Publication Date: December 30, 2014) (Patent Document 3) Authorized Patent Publication No. 10-0865692 (Invention Title: Hot Melt Film and Preparation Method Thereof. Publication Date: October 28, 2008) (Patent Document 4) Patent Publication No. 10-2006-0126672 (Invention Title: Hot Melt Adhesive Composition. Publication Date: May 8, 2006)

Claims

1. A thermoplastic hot melt film with excellent adhesion, characterized in that, The thermoplastic hot melt film comprises thermoplastic resin and nano-silica. The thermoplastic resin is selected from one of thermoplastic polyurethane, ethylene vinyl acetate, polyamide, and polyester.

2. The thermoplastic hot melt film with excellent adhesion according to claim 1, characterized in that, The nano-silica has a size of less than 100 nm, the thermoplastic hot melt film has a thickness of 0.1 to 0.2 mm, and the nano-silica content is 0.1 to 5.0 phr.

3. The thermoplastic hot melt film with excellent adhesion according to claim 2, characterized in that, The content of the nano-silica is 0.1 to 3.0 phr.

4. A method for preparing a thermoplastic hot melt film with excellent adhesion according to any one of claims 1 to 3, characterized in that, The method includes the following steps: Prepare the raw materials for polymerizing the thermoplastic resin; The nano-silica is added to the raw material and then mixed. The raw material containing the nano-silica is fed into a reactive extruder to polymerize the raw material, thereby obtaining a composition of the thermoplastic resin and the nano-silica. The composition is dried and cured, and then fed into a T-die extruder to prepare the thermoplastic hot melt film with excellent adhesion.

5. The method according to claim 4, characterized in that, The thermoplastic resin is thermoplastic polyurethane, and in the mixing step, the temperature is 80-100℃ and the stirring speed is 20-30 rpm.

6. A method for preparing a thermoplastic hot melt film with excellent adhesion according to any one of claims 1 to 3, characterized in that, The method includes the following steps: The thermoplastic resin and the nano-silica are mixed to obtain a composition of the thermoplastic resin and the nano-silica. The composition is cooled and then pulverized; The pulverized composition is fed into an extruder, extruded, and cooled to obtain a masterbatch containing the thermoplastic resin and the nano-silica; The masterbatch and another thermoplastic resin are fed into a T-die extruder to prepare the thermoplastic hot melt film with excellent adhesion.

7. The method according to claim 6, characterized in that, The thermoplastic resin is thermoplastic polyurethane. During the mixing step, the temperature is 100–120°C, and the stirring speed is 20–30 rpm. During the extrusion process, the extruder temperature is 150–200°C. During the cooling process, the cooling temperature is 15–20°C.